To solve the equation using GEMDAS rules, we need to simplify the expression inside the parentheses first.
1/4 + 1/3 can be simplified by finding a common denominator:
1/4 = (1 * 3)/(4 * 3) = 3/12
1/3 = (1 * 4)/(3 * 4) = 4/12
Now we can rewrite the equation:
11/12 - (1/4 + 1/3) = 11/12 - (3/12 + 4/12)
Next, we can add the fractions inside the parentheses:
11/12 - (3/12 + 4/12) = 11/12 - 7/12
Now we can subtract the fractions:
11/12 - 7/12 = (11 - 7)/12 = 4/12
Finally, we simplify the fraction by dividing both the numerator and the denominator by their greatest common divisor (GCD), which is 4:
4/12 = (4/4) / (12/4) = 1/3
Therefore, the solution to the equation 11/12 - (1/4 + 1/3) using GEMDAS rules is 1/3.
Solve the equation using GEMDAS rules. Show all your steps - including equivalent fractions and simplest form.
11/12 – (1/4 + 1/3)
1 answer